A Perfect Storm: High-stakes Examination and Private Tutoring in Egypt - Moreno Olmedilla, Juan Manuel (Revista Española de Educación Comparada, 2021)
This paper presents the most recent evidence on the prevalence of private tutoring in Egypt and then sets out to discuss how the 2018 “Education 2.0 Reform” is trying to change the culture of both schooling and private tutoring by the replacement of the Thanawiyya Amma examination. The political economy challenges faced by the reform are discussed together with the communication and evidence gaps, and options moving forward are identified and presented as the conclusion. In most countries and in most cases, there is a symbiotic relationship between private tutoring and public schooling systems. To a good extent, both thrive with each other. The existence of external high-stakes examinations helps and fuels such symbiosis although, in cases such as Egypt, the private tutoring industry has become so powerful that it is parasitizing public schooling and somehow supplanting it. Empty secondary classrooms in the last two years of upper secondary education, and a volume of family investment on private tutoring that rivals that of the State in public schooling, together with a teacher force whose key salary incentives are related and dependent on the exam, all signal that the line between symbiosis and parasitism was crossed some time ago.